Five-year outcomes from a phase 3 METRIC study in patients with BRAF V600 E/K-mutant advanced or metastatic melanoma* - Robert, Caroline; Hassel, Jessica C.; Utikal, Jochen (European journal of cancer, 2019)
Background - Primary findings from the METRIC (TMT212A2301) study demonstrated that trametinib improved progression-free survival (PFS) and overall survival (OS) compared with chemotherapy in patients with unresectable or metastatic cutaneous melanoma with a BRAF V600 E/K mutation. However, clinical data characterising the long-term use of these therapies in combination with BRAF inhibitors or as monotherapies are limited. - Methods - In this open-label, phase 3 study, 322 patients with BRAF V600 E/K-mutant metastatic melanoma were randomised in a 2:1 ratio to receive trametinib (2 mg orally, once daily; n = 214) or chemotherapy (dacarbazine [1000 mg/m2] or paclitaxel [175 mg/m2] intravenously, every 3 weeks; n = 108). Patients who progressed on chemotherapy were allowed to cross over and receive trametinib. Five-year results of efficacy and safety analyses are reported. - Results - The median PFS was 4.9 months in the trametinib arm versus 1.5 months in the chemotherapy arm (hazard ratio, 0.54; 95% confidence interval, 0.41-0.73). Landmark OS rates for trametinib versus chemotherapy arms at 1 year, 2 years and 5 years were 60.9% versus 49.6%, 32.0% versus 29.4% and 13.3% versus 17.0%, respectively. Most patients (n = 70 [65%]) from the chemotherapy arm crossed over to the trametinib arm early in their treatment. No unexpected adverse events were reported. - Conclusions - This 5-year follow-up of patients with BRAF V600 E/K-mutant metastatic melanoma on a targeted therapy demonstrates that long-term use of trametinib is possible with no new or unexpected adverse events. Some patients experienced long-term survival benefit with trametinib monotherapy (METRIC ClinicalTrials.gov number, NCT01245062.).